A social force evacuation model considering the effect of emergency signs. (August 2018) - Yuan, Zhilu; Jia, Hongfei; Zhang, Linfeng; Bian, Lei
In this paper, we investigate the effect of emergency signs on evacuation dynamics under smoke conditions. We assume that in a smoky hall the visual field of pedestrians is limited to a certain range, and they do not know the exact location of the exit. In this kind of evacuation process, we analyze the influence of emergency signs on movement direction and speed, and the herd behavior of pedestrians. In the analysis, we divide the emergency signs into two types: the wall signs (WS) and the ground signs (GS). Then, we analyze the variation of pedestrian behavior when they encounter the WS, the GS, and the exit in the evacuation process. Combined with the analysis results, we build our improved model based on the social force model. In the simulation, we study the evacuation process in the case of WS and GS. According to the result of the simulation, we consider that the effect of the emergency signs on herd behavior and the desired speed is an important factor to improve evacuation efficiency. We find that, from the perspective of evacuation time, the evacuation in the case of WS is more efficient, but from the perspective of the interaction between pedestrians, the evacuation in the case of GS presents less security risk. Finally, we explore how to design a mixed layout scheme of WS and GS.